Corporate Social Responsibility Disclosure Quality and Quantity and Its Effect on Firm Value in Ghana - Alhassan Musah; Mohammed Abdulai; Bismark Okyere; Abigail Padi (Indonesian Journal of Sustainability Accounting and Management, 2022)
This study investigates the nature of Corporate Social Responsibility Disclosure (CSRD), the location of CSRD in annual reports, and identifies sectors that disclose more CSRD information among listed firms in Ghana. The study also investigated the quality and quantity of CSRD with its consequence in terms of quality and quantity of the impact on firm value. The study sampled 33 listed firms over 10 years, from 2011 to 2020. Data were analyzed using descriptive statistics, correlation analysis, and panel regression analysis. The results of the study showed the weak relationship between the quality and quantity of CSRD. Regarding the nature of CSRD, community information was disclosed more often than any other category of information was. In addition, this research study demonstrated that a separate section for CSRD information was much preferred. Further, the financial sector disclosed more CSRD information than any of the other sectors did. On the consequences of CSRD, the results showed no significant impact of CSRD on firm value in terms of either quality or quantity of CSRD. The results suggest that investors in Ghana do not pay attention to the quality and quantity of firms’ CSRD in making their investment decisions.